Multiply the first equation by 2
2x + 2y =30
now we’ll add the second equation to the first equation
2x + 2y =30
-2x+5y= -2
7y=28
divide by 7
y=4
now plug y back into the first equation
x + 4 = 15
subtract 4
x=11
Answer:
x = 30
Step-by-step explanation:
-2x + 10 +4x=70
-10 -10
-2x + 4x = 60
2x = 60
/2 /2
x = 30
Answer:
(a) (6, 2)
Step-by-step explanation:
The system of equations has one of them in y= form, so it lends itself to solution by substitution.
__
Using the equation for y to substitute into the first equation, we have ...
2x -y = 10
2x -(-1/2x +5) = 10 . . . . . substitute for y
2x +1/2x -5 = 10 . . . . . eliminate parentheses
5/2x = 15 . . . . . . . . . add 5, collect terms
x = 6 . . . . . . . . . . . multiply by 2/5
Using the equation for y, we have ...
y = -1/2(6) +5 = -3 +5
y = 2
The solution is (x, y) = (6, 2).
Answer:
$180
Step-by-step explanation:
100%=x
35%=$63
63 x 100=6300/35=$180